Jus semangka menurunkan kadar asam urat - afridah, wiwik; sari, catur ertika (Universitas Nahdlatul Ulama Surabaya, 2013)
Abstract: As the population of the elderly increases, health problems such as Gout indicated by Hyperuricemia might also appear. Hyperuricemia can be prevented by increasing the intake of Vitamin C, B5, B6, and E. Therefore, the purpose of this research was to find out the effects of watermelon juice on the change in uric acid level in the elderly living in Dupak Bangunsari RT V RW 4 Surabaya. The research used quasi- experiment design. The populations involved 16 old people with Hyperuricemia, in which half of them, 8 people, were taken as the samples done by applying the random allocation technique classified as follows: 8 people in experiment group and 8 people in control group. The watermelon juice therapy was chosen as the independent variable, where as the dependent variable was the change of uric acid level. Furthermore, the uric acid level measuring tool was used to collect the data which were then recorded on the recapitulation and watermelon juice sheet. The result of analysis done by applying Fischer?s Exact test and SPSS for Windows showed that ? = 0.001 < ? = 0.05 which meant that the research hypothesis was accepted illustrating that there were some effects of watermelon juice on the change in uric acid level in the elderly living in the above mentioned region. The research has come to a conclusion that there were some effects of watermelon juice on the change in uric acid level. Hence, the old people with Hyperuricemia should consume more Vitamin C, B5, B6, and E and change their life pattern into the healthy one.